National alert campaign about increased cholesterol: determination of cholesterol levels in 81,262 Brazilians - Martinez,Tania L. Rocha (2003)
OBJECTIVE: To determine the levels of total cholesterol in a significant sample of the Brazilian population. METHODS: Blood cholesterol was determined in 81.262 individuals > 18 years old (51% male, 44.7 ± 15.7 years), using Accutrend equipment, in the cities São Paulo, Campinas, Campos do Jordão, São José dos Campos, Santos, Santo André, Ribeirão Preto, Porto Alegre, Rio de Janeiro, Belo Horizonte, Curitiba, Brasília, Salvador and documented in the presence of other risk factors (RF) for coronary artery disease (CAD) (systemic hypertension, CAD in the family, smoking, and diabetes). Participants were classified according to sex, age, and the presence or absence of RF, respectively, as 0 RF, 1 RF and > 2 RF. The percentage of individuals with cholesterol > 200 mg/dL and > 240 mg/dL was evaluated. RESULTS: The prevalence of individuals with 0, 1, and > 2 risk factors was 30% (n = 24,589), 36% (n =29,324), and 34% (n = 27,349) respectively, (P=0.657), and the mean total cholesterol of the population was 199.0 ± 35.0 mg/dL. Cholesterol levels above 200 and 240 mg/dL were found, respectively, in 40% (n = 32,515) and 13% (10.942) of individuals. The greater the number of risk factors the higher the levels of cholesterol (P<0.0001) and the greater the proportion of individuals with cholesterol > 200 mg/dL (P=0.032). No difference existed in the proportion of individuals with cholesterol > 240 mg/dL (P=0.11). CONCLUSION: A great percentage of individuals with cholesterol levels above those recommended to prevent coronary artery disease was found.